Semantics of Power in the Academic Research Process: A Phenomenological Analysis of the Experiences of Students and Graduates of Tehran University - Ramin Najafi (Alzahra University, 2021)
Since power relations in academic research, especially group and team research, are undeniable, identifying the semantics of power in the research process using the experiences of students and graduates has been the purpose of this study. Since the exploration and description of the experiences of students and graduates from the meaning and concept of power in the research process has been the purpose of the research, the research plan is qualitative. In this research, graduate students have formed the study population; because students are mainly targeted by the power of professors. The sampling method of the present study is non-targeted and criterion-based. Based on this, students and graduates participated in this research to have the criterion of team research experience, availability and agreement to conduct the interview. A semi-structured interview was conducted with 19 students and graduates of the University of Tehran. In order to analyze the data, the Stokes-Colaizzi-Kane analysis method was used. The researcher's long-term and continuous participation in the research, avoiding early conclusions and reviewing the research colleagues have been the most important actions of the researchers in order to realize the validity and reliability of the research findings. Students and graduates believe that power in the research process can be positive, negative and even neutral, and it can also be guiding or inhibiting. Ethics, freedom of action, overt control, latent control, irresponsibility, influence, cooperation and support and guidance have been identified as meanings of power in the research process. Based on the research findings, due to the lack of positive experience about the influence of research supervisors on students, in order to effectively manage the research process, it is suggested that they consider leadership styles in this process.